FROM CLASSROOM TO CLINIC: AN ESP NEEDS ANALYSIS FOR MIDWIFERY STUDENTS - Wirawati, Wahyu Adri; Laili, Roudlotun Nurul; Nashir, Muhammad (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
The increasing globalization of healthcare requires midwives to develop effective English communication skills since it has become the standard of international communication in healthcare facilities. This research aims to evaluate the English language needs of midwifery students and identify gaps in current instructional practices. The research design was qualitative, and data was collected through questionnaire responses, semi-structured interviews, and document analysis. The samples included 30 participants from midwifery students, instructor, and clinical supervisor. The findings indicated that all students acknowledged medical terminology and patient communication skills as vital subjects. Students expressed anxiety and a lack of readiness using English in clinical settings because of the substantial difference between classroom learning and real-world practice. The study finds that English for Specific Purposes (ESP) curricula do not adequately address the precise linguistic requirements that characterize midwifery practice. Developing curricula for midwifery students should use authentic material and contextualized scenarios, integrated with language training by clinical supervisors and support from educators, may assist students in real-world engagement to enhance clinical care across settings. Future research should examine larger factors that shape language education in health services.